The multiple spirals in the disk of HD100546. Issue Volume 8:Issue S299(2013) (6th January 2014) - Boccaletti, A.; Lagrange, A.-M.; Pantin, E.; Augereau, J.-C.; Quanz, S. P.; Meheut, H.
Abstract: We report the detection of multi-armed spirals in the environment of HD 100546 using NICI at Gemini South in the Ks band. These data feature a better angular resolution and higher contrast than previous HST images, which allows to resolve the former known spiral into a multiple pattern. An analytic model with a gravitational perturber is used to fit the spiral pattern. We derived limit of detections which set constraints on the discovered forming planet.